Stochastic dynamic response analysis of submerged multi-body structure considering the uncertainty of connection gap. (September 2019) - He, Kongde; Zhou, Pengfei; Fang, Zifan; Yang, Weihua; Liu, Shaopeng
The aim of this study is to determine the stochastic dynamic characteristics of the system due to the uncertainty of the gap contact between the mooring cable and the structural body of the submerged multi-body structure. The sag effect caused by the light, flexible, and low damping characteristics of the mooring cable and its dynamic elongation under the action of the flow field and the impact of the gap connection is considered. The sag effect is corrected using the equivalent elastic modulus method; the stochastic generalized non-deterministic dynamic model of the system considering the dynamic elongation and clearance contact of the mooring cable is established; and the Newmark-β method and the interval algorithm are used to solve the problem. The calculation results show that the mean and peak values of the kinematic parameters of the structure are larger than the ideal articulated state; the dynamic tension is changed randomly; and the deflection angle of the gap-contact state is greater than that of the articulated state, which may lead to the instability of the system. Therefore, when studying the concrete structure in water, we should consider the contact state of the joint and analyze its stochastic dynamic characteristics.